2003
DOI: 10.1038/sj.ijir.3900944
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind, randomised- placebo, controlled, parallel group, multicentre, flexible-dose escalation study to assess the efficacy and safety of sildenafil administered as required to male outpatients with erectile dysfunction in Korea

Abstract: The efficacy and safety of sildenafil was evaluated in a randomiSed, double-blind, placebocontrolled, flexible-dose study in Korean men aged 28-78 y with erectile dysfunction (ED) of broadspectrum aetiology and more than 6 months duration. A total of 133 patients were randomised at six centres in Korea to receive either sildenafil (50 mg initially, increased if necessary to l00 mg or decreased to 25 mg depending on efficacy and tolerance) (n ¼ 66) or matching placebo (n ¼ 67) taken on an 'as needed' basis l h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 16 publications
0
21
1
Order By: Relevance
“…In other Korean studies, 32 and 23% of patients reported hot flushes and headaches, respectively. 7 In contrast, in the present study, figures ALT denotes alanine aminotransferase, CPK denotes creatinine phosphokinase.…”
Section: Discussioncontrasting
confidence: 39%
See 2 more Smart Citations
“…In other Korean studies, 32 and 23% of patients reported hot flushes and headaches, respectively. 7 In contrast, in the present study, figures ALT denotes alanine aminotransferase, CPK denotes creatinine phosphokinase.…”
Section: Discussioncontrasting
confidence: 39%
“…Given that ED is usually linked with cardiovascular risk factors, 6 it is likely that the incidence of ED will increase in future and lead to the increased use of sildenafil for treatment of this condition. Recently published clinical trial results 7 showed that the efficacy and safety of sildenafil prescribed to Korean patients was similar to that reported in other countries. [8][9][10] However, the main focus of such trials was the efficacy of sildenafil prescribed in tertiary care facilities, such as in male health clinics and by urologists, and, as such, those results may differ from results in primary care institutions.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…The dose in Japan has been regulated by the result of a clinical trial for the efficacy of sildenafil, which failed to demonstrate the superiority of 100 to 50 mg. 18 In addition, in our current study, 90% of responders achieved efficacy with 25 or 50 mg of sildenafil. As for other Asian countries, 65% of the patients were satisfied with 100 mg sildenafil in Korea, 19 and 47% in Singapore. 20 In all, 100 mg Sildenafil leads to an increase of adverse events such as blurred vision in 11.1%, compared with 2.2% for the dose of 50 mg. 21 Moreover, 40% of sildenafil nonresponders responded to the same dose after the re-education by ED specialists, including the timing of taking the drug or prevention of interaction with food.…”
Section: Discussionmentioning
confidence: 99%
“…The study population included only the patients in whom we could assess the treatment outcome at the In some previous studies, the clinical outcomes were assessed by global efficacy questions that asked patients about the effect of sildenafil on sexual function and about their satisfaction with treatment. 1,2,5,19,20 Therefore, in terms of patients' satisfaction with the drug, a validated questionnaire might not always be necessary. Nevertheless, we will assess the definite erectile function with a validated questionnaire in a future study.…”
Section: Discussionmentioning
confidence: 99%